LAW AND LITERATURE: FROM THE SPECIFIC TO THE INTERDISCIPLINARY - Juan Ruiz, Julio (2026)
This paper aims to reflect on the interdisciplinary relationship between law and literature from the theoretical bases of these two areas. From this perspective, we will begin by examining how the matrices of both disciplines were constructed. This delimitation was made in the first decades of the last century by Hans Kelsen and the group of literary theorists known as the “Russian Formalists”. While this work was fruitful, in some cases it led to a disciplinary isolation that resulted in self-sufficient positions that impeded interdisciplinary relationships. For this reason, we propose, both in the fields of law and literature, to analyze the relationships between both disciplines by examining dialogical positions that made interdisciplinary relationships possible. In a special way, they also paved the way for considering the possible contributions of literary categories to the legal field.